Biochemical and Cellular Specificity of Peptide Inhibitors of G Protein-Coupled Receptor Kinases - Baameur, Faiza (Int J Pept Res Ther, 2014)
Identifying novel allosteric inhibitors of G protein-coupled receptor kinases (GRKs) would be of considerable use in limiting both the extent of desensitization of GPCRs as well as downstream positive regulation through GRKs. Several peptides have previously been identified as inhibitors of specific GRKs, but to date there have been few comparisons of the selectivities of these materials on the seven GRKs, modifications to allow cell penetration, or off-target activities. The goal of this study was to determine if a panel of peptides mimicking domains on either GPCRs or GRKs would exhibit selective inhibition of GRKs 2, 5, 6 and 7 phosphorylation of rhodopsin. Peptides included sequences from GRK5; helices 3, 9, and 10 (α3, α9, and α10) in the RH domain, and the N-terminal peptide (N-Ter), as well as the intracellular loop 1 (iL1) of the β2-adrenergic receptor (β2AR), and the G(α) transducin C-tail (TCT). While some selectivity for individual GRKs was found, overall selectivity was limited and often not reflective of structural predictions. Off-target effects were probed by determining peptide inhibition of adenylyl cyclase (AC) and PKA, and while peptides had no effect on AC activity, N-Ter, iL1, and α10 were potent inhibitors of PKA. To probe inhibition of GRK activity in intact cells, we synthesized TAT-tagged peptides, and found that TAT-α9-R169A and TAT–TCT inhibited isoproterenol-stimulated GRK phosphorylation of the β2AR; however, the TAT peptides also inhibited isoproterenol and forskolin stimulation of AC activity. Our findings demonstrate potent peptide inhibition of GRK activities in vitro, highlight the differences in the environments of biochemical and cell-based assays, and illustrate the care that must be exercised in interpreting results of either assay alone.